Testing the Spirits? The Theological Controversy Surrounding David Yonggi Cho and the World's Largest Church, 1983–1994 - Seo, Dongjun (Studies in world christianity, 2025)
During the 1980s, Yoido Full Gospel Church, founded by David Yonggi Cho, experienced explosive expansion in its membership, coinciding with one of the most challenging theological controversies in its history. This controversy reached its peak in 1983 when one of Korea's largest Protestant denominations, the Presbyterian Church in Korea (Tonghap), declared Cho heretical. It subsided after the denomination withdrew this decision in 1994. The critiques against Cho were primarily related to his interpretations of the Holy Spirit and spiritual beings: allegations concerning Cho's emphasis on divine healing, speaking in tongues, and material blessings and success, as well as his stance toward ancestral veneration. Despite the controversy's significance in shaping Cho's theology, in fostering understanding of Pentecostal Christianity in the Korean context, and in raising the broader issue of the Holy Spirit's work, detailed historical analysis of this controversy has been neglected. This article, drawing from an extensive examination of Korean primary sources largely unutilised in English scholarship, delves into why and how the controversy arose. It also explores the key accusations against Cho concerning the Holy Spirit and spiritual beings, as well as the broader implications of the controversy.